Pemberdayaan Nelayan Tradisional Lhok Meureubo melalui Pembuatan dan Pemanfaatan Teknologi Bubu Dasar Berbasis Ramah Lingkungan sebagai Upaya Meningkatkan Hasil Tangkapan - Afdhal Fuadi; Rosi Rahayu; Muhammad Rizal; Randi Ujirta; Adima Yuslil; Rukiah Situmorang; Fachrurozi Amir (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Meureubo is one of four sub-districts in West Aceh Regency that borders directly on the sea. Fishermen in the Lhok Meureubo area are traditional fishermen with fishing vessels measuring under 5 GT and operational areas under 2 nautical miles. Currently, fishermen use gillnets and handlines to catch reef fish. However, this fishing gear is considered insufficient because it requires a lot of time and energy. Bottom traps are optimal fishing gear for catching fish at the bottom of the waters, such as reef fish, and their use also does not require a lot of time and energy, and the tools and materials used are based on local resources that are environmentally friendly for the marine waters of West Aceh Regency. The purpose of this community service is to provide education and understanding for fishermen about the manufacture and use of bottom traps. The number of participants was 40 people who are traditional fishermen of Lhok Meureubo. The implementation method was socialization regarding the use and advantages of bottom traps and provided a workshop on making and assembling bottom traps. The results of this community service program were an 80% increase in fishermen's understanding and knowledge of bottom trap use and an 85% increase in skills in assembling and manufacturing the bottom trap technology. A total of 11 bottom traps were successfully manufactured, which will be operated directly by traditional fishermen from Lhok Meureubo in the waters of West Aceh Regency.